Crystal Defects and Cation Redistribution Study on Nanocrystalline Cobalt-Ferri-Chromites by Positron Annihilation Spectroscopy. (10th June 2013) - Modi, Kunal B.; Vasoya, Nimish H.; Lakhani, Vinay K.; Pathak, Tushar K.; Nambissan, P. M. G.
Abstract : Positron lifetime and Doppler broadening measurements were carried out on nanocrystalline (grain size 60–65 nm) samples of the Cr 3+ -substituted cobalt ferrite system with general chemical formula CoCr x Fe2− x O4 (x = 0.0 −2.0) synthesized by the coprecipitation technique. The results indicated selective trapping of positrons in large vacancy clusters initially at the tetrahedral (A-) sites and then with Cr 3+ -substitution up to concentration( x ) = 0.7, at the octahedral (B-) sites. The results are consistent with the cation distribution determined from X-ray diffraction line intensity calculations, which indicated partial inversion of the inverse spinel ferrite, subsequent stabilization over a range of substitution (x = 0.7 to 1.7), and finally the full inversion to the normal spinel chromite (CoCr2 O4, x = 2 . 0 ). In the intermediate range of substitution, lattice contraction prevented a fraction of Co 2+ ions released from the (B-) sites from entering the tetrahedral sites, and these vacancies at the (A-) sites trapped positrons. Although the samples were composed of nanocrystalline grains, only an insignificant fraction of positrons were diffused and annihilated at the grain surfaces, since the grain sizes and the thermal diffusion length of positrons nearly overlapped.